Method and system for determining application mixing amount of solid waste powder material in asphalt pavement

By preparing and processing stone slabs, preparing adhesion performance test specimens, and conducting environmental coupled aging and multi-point loading tests, the problem of single indicators of adhesion analysis methods in the existing technology and inability to recombinate by multiple factors is solved, and a comprehensive and systematic evaluation of adhesion parameters of solid waste sulphur materials in asphalt pavement materials is achieved, the optimal dosage is determined, and the application value is improved.

CN119827751AActive Publication Date: 2025-04-15GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510116068.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The method of analyzing adhesion at this stage has the disadvantage of single indicators and multi-factors inability to recombinate, and it has not been able to comprehensively and systematically evaluate the adhesion of aggregate-asphalt.

Method used

By preparing fixed-size stone slabs, the adhesion surface of the stone slab is processed, adhesion performance test specimens are prepared, and environmental coupling aging treatment and multi-point loading test are carried out. The optimal dosage of solid waste sulphur material in asphalt pavement materials is determined based on the adhesion parameter indicators.

Benefits of technology

Through comprehensive analysis of multiple indicators, the adhesion of asphalt slurry of solid waste slurry can be comprehensively and systematically reflected, the optimal filler application dosage can be determined, and the application value of solid waste slurry materials in road construction is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827751A_ABST
    Figure CN119827751A_ABST
Patent Text Reader

Abstract

The invention discloses a method and system for determining the application mixing amount of a solid waste powder material in an asphalt pavement, and relates to the technical field of road material performance evaluation.The method comprises the following steps that a stone plate with the fixed size is prepared, and the adhesion face of the stone plate is treated; preparing an adhesion efficiency test piece; carrying out environmental coupling aging treatment on the adhesion efficiency test piece; carrying out a multi-point loading test on the adhesion performance test piece, and obtaining test data; and determining the optimal mixing amount of the solid waste powder material in filling application of the asphalt pavement material based on the adhesion parameter index. According to the method disclosed by the invention, the improvement efficiency of the solid waste powder material on the content of the structural asphalt is evaluated by taking an adhesion parameter index of a stone slab and asphalt mortar aging adhesion test piece as an evaluation basis, so that the optimal mixing amount of the solid waste powder material in filling application in an asphalt pavement material is determined; and a related basis is provided for resource utilization of solid waste powder materials in road engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road material performance evaluation, and in particular to a method and system for determining the dosage of solid waste powdery materials used in asphalt pavement. Background Art

[0002] With the improvement of economic development level and the advancement of urbanization, the amount of solid waste powder materials generated in my country has increased year by year, occupying a large amount of land resources and posing a great ecological and environmental safety hazard. The comprehensive utilization of solid waste powder materials can effectively improve resource utilization and promote high-quality development. Using solid waste as filler for asphalt mixture can improve the performance of the mixture on the one hand, and reduce the consumption of traditional building materials and improve the utilization rate of solid waste on the other hand, fundamentally reducing the impact of solid waste on the environment and reducing the cost of road construction, which has positive significance for environmental protection and road construction.

[0003] The interfacial interaction between asphalt and aggregate has an important influence on the performance of asphalt mixture, and adhesion is a key factor. Asphalt forms a thin film covering the surface of aggregate particles to achieve effective bonding to the aggregate, which is not only related to the overall bonding of the mixture, but also directly related to the performance and life of the pavement. Existing studies have shown that using solid waste powder materials as fillers in asphalt mixtures can improve their adhesion, thermal stability and aging resistance. However, the types and characteristics of solid waste powder materials are diverse, and their effects on the adhesion between asphalt and aggregate have not been systematically studied in depth. At present, the methods for analyzing adhesion have the disadvantages of a single indicator and the inability to combine multiple factors, and cannot comprehensively and systematically evaluate the adhesion of aggregate-asphalt. Therefore, there is an urgent need for a method for determining the application amount of solid waste powder materials in asphalt pavement materials. The adhesion of solid waste powder materials asphalt and aggregates can be evaluated by multi-indicator correlation, so as to determine the optimal filler application amount of solid waste powder materials, so as to facilitate the promotion and application of solid waste powder materials in road construction. Summary of the invention

[0004] In view of the problems existing in the determination of the dosage of existing solid waste powdery materials used in asphalt pavement and in the system, the present invention is proposed.

[0005] Therefore, the problem to be solved by the present invention is that the current method for analyzing adhesion has the disadvantages of single index and inability to combine multiple factors, and is unable to comprehensively and systematically evaluate adhesion.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: In a first aspect, an embodiment of the present invention provides a method for determining the dosage of solid waste powdery materials used in asphalt pavement, which comprises the following steps: Prepare stone slabs of fixed size and treat the adhesive surface of the stone slabs; preparing adhesion performance test specimens; The adhesion performance test specimens were subjected to environmental coupling aging treatment; Conduct multi-point loading test on the adhesion performance test specimen and obtain test data; The optimal dosage of solid waste powdery materials as fillers in asphalt pavement materials is determined based on adhesion parameter indicators.

[0007] As a preferred solution of the method for determining the dosage of solid waste powdery materials used in asphalt pavement according to the present invention, the step of treating the adhesion surface of the stone slab includes: The stone slab is cut using a laser cutting machine, and one side of the stone slab is used as the adhesive surface, and then it is polished using a CNC grinder. After polishing, the stone slab is placed in an ultrasonic cleaning machine and cleaned at 60°C for 20-30 minutes to remove powder and dust on the surface; Place the cleaned slab in a 100°C oven and dry for 1h-2h; Use a roughness meter to measure the roughness of the adhesion surface of the stone slab, and test the roughness of the center position of the adhesion surface and the midpoints of the four sides respectively. Take the average value of the test results as the roughness of the polished surface of the stone slab; When the roughness is less than 5μm, it meets the standard. When the roughness is not less than 5μm, the grinding is repeated until the roughness index meets the requirements. The prepared stone slabs are placed in an oven at 180°C-200°C for heating and standby use.

[0008] As a preferred solution of the method for determining the dosage of solid waste powdery materials in asphalt pavement according to the present invention, the step of preparing the adhesion performance test specimen comprises: Preheat asphalt and solid waste powder materials to 135°C ± 1°C, weigh the solid waste powder according to the powder-to-binder mass ratio of 0.6, 0.8, 0.1, 1.2, and 1.4, add the weighed solid waste powder to the molten asphalt, and use a high-speed shearing instrument to shear the mixture at high speed to prepare solid waste powder-asphalt mortars with different powder-to-binder ratios; Take out the stone slab from the oven, place it in the 3D printer with the adhesive surface facing upward, pour the pre-prepared solid waste powder-asphalt slurry into the feed port of the 3D printer, and use the parallel printing mode to print an evenly distributed asphalt film with a thickness of 1-3mm on the adhesive surface of the stone slab. Then take out another stone slab from the oven, and attach it to the asphalt film with the adhesive surface facing downward to obtain the finished product; Place the finished product at the center of the rectangular tube, and place a steel plate on the finished product, and place a weight of 5-10kg at the center above the steel plate. Place the finished product, the rectangular tube, and the weight in a 60°C oven and let it stand for 1h-2h. When the steel plate and the rectangular tube are attached, the thickness of the asphalt film between the stone slabs no longer changes. At this time, take out the finished product and let it stand for 3-5h at room temperature. The thickness of the asphalt film was measured by a spiral micrometer, and the thickness of the asphalt film between the stone slabs was controlled at 1±0.05 mm. A hot scraper was used to scrape off the asphalt overflowing between the stone slabs to obtain the adhesion performance test specimen.

[0009] As a preferred solution of the method for determining the dosage of solid waste powdery materials in asphalt pavement according to the present invention, the step of subjecting the adhesion performance test specimen to environmental coupling aging treatment includes: Place the adhesion performance test specimen into the ultraviolet light accelerated weathering tester with the side facing the ultraviolet radiation light source; Manually adjust the placement of the adhesion performance test specimen every 82.5 hours, and change other sides to face the ultraviolet radiation light source, so that each side of the adhesion performance test specimen can be evenly exposed to ultraviolet aging; After aging, the adhesion performance test specimens were placed at room temperature for curing for 6-12 hours.

[0010] As a preferred solution of the method for determining the dosage of solid waste powdery materials in asphalt pavement according to the present invention, the step of obtaining test data includes: The two tensile test molds 2 are bonded to the upper and lower surfaces of the adhesion performance test specimen using an epoxy resin adhesive; According to the requirements of different loading conditions, epoxy resin adhesive is evenly applied on the bottom and side surfaces of the loading point of the tensile test mold 1 to be bonded, and then bonded to the holes of the loading point on the upper end of the tensile test mold 2. After bonding, the tensile test mold 1 is fixed in a 20KN electro-hydraulic servo fatigue testing machine, and a cyclic dynamic load is applied to the morphological index specimen to simulate the repeated changes of the actual traffic load. Static loads are applied to the mechanical index specimen and the control specimen to test their bonding strength until the asphalt film between the adhesion performance test specimens is completely separated; The requirements for loading conditions include the first condition, the second condition, and the third condition.

[0011] As a preferred solution of the method for determining the dosage of solid waste powder material in asphalt pavement according to the present invention, wherein: the adhesion parameter index is the asphalt adhesion rate of the morphological index specimen under different loading conditions. , morphology index I1, mechanical index specimen failure work , mechanical index I2 and the failure work W of the control specimen 0i , aging resistance rate Ui , aging index I3.

[0012] As a preferred solution of the method for determining the dosage of solid waste powdery materials in asphalt pavement application according to the present invention, the method for determining the optimal dosage of solid waste powdery materials as fillers in asphalt pavement materials includes: Draw radar charts of morphological index I1, mechanical index I2 and aging index I3; Calculate the area S of the radar chart and determine the optimal filler application amount of solid waste powdery materials by comparing the area sizes; Wherein, the asphalt adhesion rate The calculation formula is as follows: ; In the formula, is the asphalt adhesion rate, which represents the ratio of asphalt pixel area to total pixel area. The larger it is, the better the adhesion performance of the morphology index specimen; i is the number of different loading conditions; X1 and X2 are the pixel areas of asphalt on the upper and lower adhesion surfaces of the morphology index specimen; X is the sum of the pixel areas of the adhesion surface in the loading point images of the upper and lower adhesion surfaces of the morphology index specimen; The calculation formula of the morphology index I1 is as follows: ; In the formula, is the morphological index; is the average value of asphalt adhesion rate of the morphological index specimens under different loading conditions; is the average asphalt adhesion rate of the specimens with different solid waste powder content and morphological index The maximum value in ; is the average asphalt adhesion rate of the specimens with different solid waste powder content and morphological index The minimum value in ; The destructive work The calculation formula is as follows: ; In the formula, is the work of destruction, which represents the area under the load-displacement curve of the mechanical index specimen, and its unit is J. The larger the value, the better the adhesion performance of the mechanical index specimen; i is the number of different loading conditions; F(x) is the load as a function of displacement x in the load-displacement curve of the mechanical index specimen; L is the maximum destructive tensile force F in the load-displacement curve max The corresponding displacement in the load-displacement diagram; The mechanical index I2 is calculated as follows: ; In the formula, is the mechanical index; is the average value of the failure work of the mechanical index specimens under different loading conditions; is the average failure work of mechanical index specimens with different solid waste powder content The maximum value in ; is the average failure work of mechanical index specimens with different solid waste powder content The minimum value in ; The aging resistance rate U i The calculation formula is as follows: ; In the formula, is the aging resistance rate of the control specimen under different loading conditions; i is the number of different loading conditions; The failure work of the mechanical index specimen under different loading conditions; To compare the failure work of the specimen under different loading conditions; The calculation formula of the aging index I3 is as follows: ; in, is the aging index; is the average value of the aging resistance rate of the control specimens under different loading conditions; The average aging resistance rate of the control specimens with different solid waste powder dosages The maximum value in ; The average aging resistance rate of the control specimens with different solid waste powder dosages The minimum value in ; The calculation formula of the radar chart area S is: ; ; ; ; Among them, S is the total area of ​​the radar chart, with the center point of the radar chart as the origin O, the morphological index I1, mechanical index I2, and aging index I3 correspond to points A, B, and C on the radar chart, respectively. They are located on the ray starting from the origin, and the distances from the origin are a, b, and c, respectively; S OAB is the area of ​​the triangle formed by points O, A, and B in the radar chart; S OBC is the area of ​​the triangle formed by points O, B, and C in the radar chart; S OAC It is the area of ​​the triangle enclosed by points O, A, and C in the radar chart.

[0013] In a second aspect, an embodiment of the present invention provides a system for determining the dosage of solid waste powdery materials used in asphalt pavement, which includes a slate preparation module, an adhesion performance test specimen preparation module, a multi-point loading test module, an environmental coupling aging treatment module, and an optimal dosage determination module; The slab preparation module is used to prepare slabs of fixed size and process the adhesion surface of the slabs; The adhesion performance test specimen preparation module prepares specimens for adhesion performance testing; The environmental coupling aging treatment module performs environmental coupling aging treatment on the adhesion performance test specimen; The multi-point loading test module performs a multi-point loading test on the adhesion effectiveness test specimen and obtains test data; The optimal dosage determination module determines the optimal dosage of solid waste powdery materials for use as fillers in asphalt pavement materials based on adhesion parameter indicators.

[0014] In a third aspect, an embodiment of the present invention provides a computer device, comprising a memory and a processor, wherein the memory stores a computer program, wherein: when the processor executes the computer program, it implements any step of the above-mentioned method for determining the dosage of solid waste powdery material in asphalt pavement.

[0015] In a fourth aspect, an embodiment of the present invention provides a computer-readable storage medium having a computer program stored thereon, wherein: when the computer program is executed by a processor, any step of the above-mentioned method for determining the dosage of solid waste powdery material to be used in asphalt pavement is implemented.

[0016] The beneficial effects of the present invention are as follows: by subjecting the adhesion performance test specimens to coupled aging, static and dynamic multi-point loading treatments, the evaluation of the adhesion of solid waste powdery materials to asphalt is made more consistent with the adhesion conditions of asphalt mortar and aggregate in actual pavement materials, and the multi-indicator comprehensive analysis results are highly accurate, and can comprehensively and systematically reflect the adhesion of asphalt mortar of solid waste powdery materials, determine the optimal filler application dosage of solid waste powdery materials in asphalt pavement materials, and have good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them: Figure 1 It is a flow chart of the technical solution of the present invention.

[0018] Figure 2It is a three-dimensional diagram of the adhesion performance test specimen of the present invention.

[0019] Figure 3 It is a front view of the rectangular tube and steel plate of the present invention.

[0020] Figure 4 It is a top view of the rectangular tube and steel plate of the present invention.

[0021] Figure 5 It is a front view of the tensile test die 1 of the present invention.

[0022] Figure 6 It is a top view of the tensile test mold 1 of the present invention.

[0023] Figure 7 It is a bottom view of the tensile test mold 1 of the present invention and the coordinate position of the loading point.

[0024] Figure 8 It is a front view of the tensile test mold 2 of the present invention.

[0025] Fig. 9 It is a top view of the tensile test mold 2 of the present invention.

[0026] Fig.10 It is a schematic diagram of a tensile test of an adhesion performance test specimen of the present invention.

[0027] Fig.11 It is a schematic diagram of radar chart area calculation of the present invention.

[0028] Fig.12 It is the radar chart corresponding to the adhesion efficiency test specimens of various solid waste powder dosages in the embodiments of the present invention.

[0029] In the figure, 1. tensile test mold 1; 2. tensile test mold 2; 3. stone slab; 4. solid waste powder-asphalt mortar. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the drawings of the specification. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary persons in the art without creative work should fall within the scope of protection of the present invention.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] The present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0034] At the same time, in the description of the present invention, it should be noted that the directions or positional relationships indicated by the terms "upper, lower, inner and outer" are based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting the present invention. In addition, the terms "first, second or third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0035] In the present invention, unless otherwise clearly specified and limited, the terms "install, connect, connect" should be understood in a broad sense, for example: it can be a fixed connection, a detachable connection or an integral connection; it can also be a mechanical connection, an electrical connection or a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0036] Example 1 Reference Figure 1 to Figure 12 , which is the first embodiment of the present invention, provides a method for determining the dosage of solid waste powdery materials used in asphalt pavement, comprising the following steps: S1. Prepare stone slabs of fixed size and treat the adhesive surface of the stone slabs.

[0037] The steps for treating the adhesive surface of the stone slab include: A laser cutting machine was used to cut a stone slab with a size of 100 mm × 100 mm × 50 mm. The surface of the stone slab with a size of 100 mm × 100 mm was used as the adhesion surface, and it was polished using a CNC grinder. After polishing, the stone slab was placed in an ultrasonic cleaning machine and cleaned at 60°C for 30 minutes to remove powder and dust on the surface. Place the cleaned slab in a 100°C oven for 2 hours and measure the actual thickness of the slab using a micrometer. Test the center of the top and bottom surfaces of the slab and the midpoints of the four sides, and take the average value as the actual thickness h0 of the slab. Use a roughness meter to measure the roughness of the adhesion surface of the stone slab, and test the roughness of the center position of the adhesion surface and the midpoints of the four sides respectively. Take the average value of the test results as the roughness of the polished surface of the stone slab; When the roughness is less than 5μm, it meets the standard. When the roughness is not less than 5μm, the grinding is repeated until the roughness index meets the requirements. The prepared stone slabs were placed in an oven at 200°C for heating.

[0038] In this embodiment, the stone slab is made of common stones such as basalt, limestone and limestone; the cutting machine is a CNC laser cutting machine with a working width of 6000mm×3000mm and a working power of 1000W; the CNC grinder is a CNC surface grinder with parameters set to a speed of 1500rpm, a feed speed of 100mm / min, a cutting speed of 0.2mm, and a pressure of 50N / cm 2 , the coolant flow rate is 10L / min; the micrometer is a mechanical micrometer with a measurement accuracy of 0.01mm and a measurement range of 25-50mm; the roughness meter is the Light Easy Measurement TR200 surface roughness meter.

[0039] S2. Prepare adhesion performance test specimens.

[0040] Preheat asphalt and solid waste powder materials to 135°C ± 1°C, weigh the solid waste powder according to the powder-to-binder mass ratio of 0.6, 0.8, 0.1, 1.2, and 1.4, add the weighed solid waste powder to the molten asphalt, and use a high-speed shearing instrument to shear the mixture at high speed to prepare solid waste powder-asphalt mortars with different powder-to-binder ratios; Among them, the shear temperature is 150°C, the shear rate is 4500rpm, and the shear time is 45min; among them, the asphalt is base asphalt or modified asphalt, and the solid waste powdery material is one or more of fly ash, waste incineration fly ash, and sludge ash.

[0041] Take out the stone slab from the oven, place it with the adhesive surface facing upward into the 3D printer, pour the pre-prepared solid waste powder-asphalt slurry into the feed port of the 3D printer, and use the parallel printing mode to print a uniformly distributed asphalt film with a thickness of 1-3 mm on the adhesive surface of the stone slab. In this embodiment, the asphalt film with a thickness of 1 mm is preferred, and then take out another stone slab from the oven, and attach it with the adhesive surface facing downward onto the asphalt film to obtain the finished product; Place the finished product at the center of the rectangular tube, and place a steel plate on top of the finished product, and place a weight of 10 kg at the center of the steel plate. Place the finished product, the rectangular tube, and the weight in a 60°C oven and let it stand for 2 hours. When the steel plate and the rectangular tube are attached, the thickness of the asphalt film between the stone slabs no longer changes. At this time, take out the finished product and let it stand for 4 hours at room temperature. The thickness of the asphalt film was measured by a spiral micrometer, and the thickness of the asphalt film between the stone slabs was controlled at 1±0.05 mm. A hot scraper was used to scrape off the asphalt overflowing between the stone slabs to obtain the adhesion performance test specimen.

[0042] Nine adhesion performance test specimens were prepared for each solid waste powder material dosage, including three morphological index specimens, three mechanical index specimens and three control specimens. The 3D printer is a RepRap Mendel90 3D printer. The extrusion nozzle with a diameter of 2mm is selected, the printing speed is set to 5mm / s, the printing temperature is 150℃, the width of the printed asphalt strip is 2.5mm, and the thickness is 1mm. 40 asphalt strips with a width of 2.5mm and a length of 100mm are printed to form a 100mm×100mm asphalt film plane, covering the adhesion surface of the stone slab; the steel rectangular tube with an external dimension of 160mm×160mm×101mm, an outer wall thickness of 10mm, and an internal dimension of 140mm×140mm×101mm. When the steel plate with a dimension of 160mm×160mm×10mm moves downward under the action of the weight above, it will squeeze the asphalt film between the stone slabs. When the thickness of the asphalt film is squeezed to 1mm, the steel plate will be stuck on the upper end of the steel rectangular tube, so as to achieve the purpose of controlling the thickness of the asphalt film; The method for measuring the asphalt film thickness is to use a spiral micrometer to measure the total height from the top surface to the bottom surface of the adhesion efficiency test specimen, record it as H, record the sum of the heights of the upper and lower stone slabs as h, and use Hh to represent the asphalt film thickness.

[0043] S3. Perform environmental coupling aging treatment on the adhesion performance test specimen.

[0044] Place the adhesion performance test specimen into the ultraviolet light accelerated weathering tester with the side facing the ultraviolet radiation light source; Manually adjust the placement of the adhesion performance test specimen every 82.5 hours, and change other sides to face the ultraviolet radiation light source, so that each side of the adhesion performance test specimen can be evenly exposed to ultraviolet aging; After aging, the adhesion performance test specimens were placed at room temperature for curing for 10 hours.

[0045] The environmental coupling aging treatment includes the coupling simulation of three environmental conditions: light, temperature, and precipitation. The UV accelerated weathering tester is used for coupling environmental simulation. The UV aging parameter setting irradiation intensity range is 0.6W / m2 -0.8W / m 2 The irradiation time is 330h. The adhesion efficiency test specimen is placed under the central axis of the UV aging lamp tube, 60cm away from the UV lamp tube, and the temperature parameter is 60℃; the precipitation parameter reference is 700mm, and it is achieved by spraying with a nozzle (the spraying device sprays 5mm per minute). One spray cycle is 24h, and each cycle sprays once. Each spray is 10min and about 50mm, and the number of spray cycles is 14.

[0046] S4. Perform a multi-point loading test on the adhesion performance test specimen and obtain test data.

[0047] The two tensile test molds 2 are bonded to the upper and lower surfaces of the adhesion performance test specimen using an epoxy resin adhesive; According to the requirements of different loading conditions, epoxy resin adhesive is evenly applied on the bottom and side surfaces of the loading point of the tensile test mold 1 to be bonded, and then bonded to the holes of the loading point on the upper end of the tensile test mold 2. After bonding, the tensile test mold 1 is fixed in a 20KN electro-hydraulic servo fatigue testing machine, and a cyclic dynamic load is applied to the morphological index specimen to simulate the repeated changes of the actual traffic load. Static loads are applied to the mechanical index specimen and the control specimen to test their bonding strength until the asphalt film between the adhesion performance test specimens is completely separated; Among them, when the 20KN electro-hydraulic servo fatigue testing machine loads the morphology index specimen, the loading frequency is set to 10 Hz, the loading waveform is a sine wave, and the loading stress is , stress ratio R is 0.1 (R= ); When loading the mechanical index specimens and the control specimens, the test tension range is set to 5-20KN and the loading rate is 10mm / min; Among them, refer to Figure 5~Figure 7The main body of the tensile test mold 1 is a steel cuboid with a size of 100mm×100mm×50mm. A pin head is connected to the midpoint of the upper top surface. The pin head is a cylinder with a bottom diameter of 20mm and a height of 50mm. A circular hole with a diameter of 15mm and connecting the two ends of the cylindrical side is arranged 20mm away from the top surface. The bottom surface of the large steel cuboid is connected with 17 small steel cuboids with a size of 10mm×10mm×20mm, which are used to apply multi-point tension to the adhesion efficiency test specimen. The position distribution of the raised structure of the steel cuboid takes the lower left corner of the square surface as the coordinate origin. The coordinates of the four corners of the bottom surface of the large steel cuboid are (0, 0), (0, 100), (10 0, 0), (100, 100), the coordinates of the small steel cuboid are a1 (0, 0), a2 (0, 45), a3 (0, 90), a4 (45, 0), a5 (90, 0), a6 (45, 90), a7 (90, 45), a8 (90, 90), b1 (22.5, 225), b2 (22.5, 45), b3 (22.5, 67.5), b4 (45, 22.5), b5 (67.5, 22.5), b6 (45, 67.5), b7 (67.5, 45), b8 (67.5, 67.5), c1 (45, 45), hereinafter referred to as the loading point coordinates instead of the steel cuboid position; Reference Figure 8~Figure 9 The main body of the tensile test mold 2 is a steel cuboid with a size of 110mm×110mm×60mm, and there are 17 cuboid holes with a size of 10mm×10mm×20mm on its upper surface, which are used to bond the loading points of the tensile mold 1; the lower end surface is arranged with holes with a size of 100mm×100mm×10mm, which are used to ensure that the adhesion efficiency test specimen and the mold are located on the same axis when bonding; the adhesive is epoxy resin AB glue, which is bonded by mixing A glue and B glue in a ratio of 1:1; The requirements for loading conditions include the first condition, the second condition, and the third condition. The loading point combination corresponding to the first condition includes eight loading points: a1, a2, a3, a4, a5, a6, a7, and a8. These loading points are all located at the edge of the loading surface of the adhesion efficiency test specimen, and are used to test the adhesion of solid waste powdery materials-asphalt mortar in the edge area of ​​the adhesion surface of the adhesion efficiency test specimen; the loading point combination corresponding to the second condition includes eight loading points: b1, b2, b3, b4, b5, b6, b7, and b8. These loading points are all located inside the loading surface of the adhesion efficiency test specimen, and are used to test the adhesion of solid waste powdery materials-asphalt mortar in the inner area of ​​the adhesion surface of the adhesion efficiency test specimen; the loading point combination corresponding to the third condition includes all points, and is used to test the adhesion of solid waste powdery materials-asphalt mortar of the entire adhesion efficiency test specimen; the setting function of different loading conditions is to comprehensively evaluate the bonding performance of solid waste powdery materials-asphalt mortar and improve the test accuracy.

[0048] After the tensile test of the morphology index specimen, a high-definition digital camera was used to take photos of the two stone slab adhesion surfaces of the morphology index specimen, which were imported into the Fiji-Image image processing software. The images were contrast enhanced, grayscaled, and binarized in sequence to achieve morphological separation of the asphalt and exposed stone slab areas on the adhesion surface of the morphology index specimen (black pixels were identified as asphalt, and light pixels were identified as stone slabs). The number of pixels of the asphalt, stone slab, and adhesion surface at each loading point in the image was obtained as the basic data for evaluation. After the tensile test of the mechanical index specimen and the control specimen was completed, the tension and displacement during the test were obtained as the basic data for evaluation.

[0049] S5. Determine the optimal dosage of solid waste powdery materials as fillers in asphalt pavement materials based on adhesion parameter indicators.

[0050] The adhesion parameter index is the asphalt adhesion rate of the morphological index specimen under different loading conditions. , morphology index I1, mechanical index specimen failure work , mechanical index I2 and the failure work W of the control specimen 0i , aging resistance rate U i , aging index I3.

[0051] Methods for determining the optimal dosage of solid waste powder materials as fillers in asphalt pavement materials include: Draw radar charts of morphological index I1, mechanical index I2 and aging index I3; Calculate the area S of the radar chart and determine the optimal filler application amount of solid waste powdery materials by comparing the area sizes; Among them, asphalt adhesion rate The calculation formula is as follows: ; In the formula, is the asphalt adhesion rate, which represents the ratio of asphalt pixel area to total pixel area. The larger it is, the better the adhesion performance of the morphology index specimen; i is the number of different loading conditions; X1 and X2 are the pixel areas of asphalt on the upper and lower adhesion surfaces of the morphology index specimen; X is the sum of the pixel areas of the adhesion surface in the loading point images of the upper and lower adhesion surfaces of the morphology index specimen; The calculation formula of the morphology index I1 is as follows: ; In the formula, is the morphological index; is the average value of asphalt adhesion rate of the morphological index specimens under different loading conditions; is the average asphalt adhesion rate of the specimens with different solid waste powder content and morphological index The maximum value in ; is the average asphalt adhesion rate of the specimens with different solid waste powder content and morphological index The minimum value in ; Destructive work The calculation formula is as follows: ; In the formula, is the work of destruction, which represents the area under the load-displacement curve of the mechanical index specimen, and its unit is J. The larger the value, the better the adhesion performance of the mechanical index specimen; i is the number of different loading conditions; F(x) is the load as a function of displacement x in the load-displacement curve of the mechanical index specimen; L is the maximum destructive tensile force F in the load-displacement curve max The corresponding displacement in the load-displacement diagram; The mechanical index I2 is calculated as follows: ; In the formula, is the mechanical index; is the average value of the failure work of the mechanical index specimens under different loading conditions; is the average failure work of mechanical index specimens with different solid waste powder content The maximum value in ; is the average failure work of mechanical index specimens with different solid waste powder content The minimum value in ; Aging resistance U i The calculation formula is as follows: ; In the formula, is the aging resistance rate of the control specimen under different loading conditions; i is the number of different loading conditions; The failure work of the mechanical index specimen under different loading conditions; To compare the failure work of the specimen under different loading conditions; The calculation formula of aging index I3 is as follows: ; in, is the aging index; is the average value of the aging resistance rate of the control specimens under different loading conditions; The average aging resistance rate of the control specimens with different solid waste powder dosages The maximum value in ; The average aging resistance rate of the control specimens with different solid waste powder dosages The minimum value in ; The calculation formula of radar chart area S is: ; ; ; ; Among them, S is the total area of ​​the radar chart, with the center point of the radar chart as the origin O, the morphological index I1, mechanical index I2, and aging index I3 correspond to points A, B, and C on the radar chart, respectively. They are located on the ray starting from the origin, and the distances from the origin are a, b, and c, respectively; S OAB is the area of ​​the triangle formed by points O, A, and B in the radar chart; S OBC is the area of ​​the triangle formed by points O, B, and C in the radar chart; S OAC It is the area of ​​the triangle enclosed by points O, A, and C in the radar chart.

[0052] Table 1 Morphological index K of adhesion performance test specimens i , 、I1 Table 2 Mechanical index W of adhesion performance test specimens i , 、I2 Table 3 Mechanical index W of adhesion performance test specimens 0i And aging index U i , 、I3 Table 4 Indexes I1, I2, I3 and radar chart area S of adhesion performance test specimens In this embodiment, the morphological index, mechanical index and aging index of the adhesion performance test specimen are shown in Tables 1-3; for the morphological index, the morphological index I1 reaches the maximum when the powder-to-rubber ratio is 1.2, and the order from large to small is 1.2>1.4>1.0>0.8>0.6; For mechanical index, the mechanical index I2 reaches the maximum when the powder-to-rubber ratio is 1.2, and the order from large to small is 1.2>1.0>1.4>0.8>0.6; For aging index, the aging index I3 reaches the maximum when the powder-to-rubber ratio is 1.2, and the order from large to small is 1.2>1.0>1.4>0.8>0.6; Based on the three indicators of morphological index, mechanical index and aging index, a radar chart is drawn. Fig.12As shown in Table 4, the radar chart area of ​​each solid waste powder material is obtained. The radar chart area is ranked from large to small as 1.2>1.0>1.4>0.8>0.6. Comprehensive analysis shows that the adhesion efficiency test specimen of asphalt mortar with the best solid waste powder material content is powder-to-binder ratio of 1.2; The analysis results are highly accurate and can comprehensively evaluate the adhesion performance between solid waste powder-asphalt mortar and aggregate slabs through multiple indicators, and can accurately and scientifically determine the optimal filler application amount of solid waste powder materials in asphalt pavement materials.

[0053] In summary, by subjecting the adhesion performance test specimens to coupled aging, static, and dynamic multi-point loading treatments, the evaluation of the adhesion of solid waste powdery materials-asphalt is more in line with the adhesion conditions of asphalt mortar and aggregate in actual pavement materials, and the multi-indicator comprehensive analysis results are highly accurate, which can comprehensively and systematically reflect the adhesion of asphalt mortar of solid waste powdery materials, and determine the optimal filler application dosage of solid waste powdery materials in asphalt pavement materials, which has good practical application value.

[0054] Example 2 On the basis of the first embodiment, this embodiment further provides a system for determining the dosage of solid waste powdery materials in asphalt pavement, including a slate preparation module, an adhesion performance test specimen preparation module, a multi-point loading test module, an environmental coupling aging treatment module, and an optimal dosage determination module; The slab preparation module is used to prepare slabs of fixed size and process the adhesion surface of the slabs; The adhesion performance test specimen preparation module prepares specimens for adhesion performance testing; The environmental coupling aging treatment module performs environmental coupling aging treatment on the adhesion performance test specimen; The multi-point loading test module performs a multi-point loading test on the adhesion effectiveness test specimen and obtains test data; The optimal dosage determination module determines the optimal dosage of solid waste powdery materials for use as fillers in asphalt pavement materials based on adhesion parameter indicators.

[0055] This embodiment also provides a computer device, which is suitable for the method of determining the dosage of solid waste powdery materials used in asphalt pavement, including a memory and a processor; the memory is used to store computer-executable instructions, and the processor is used to execute computer-executable instructions to implement the method of determining the dosage of solid waste powdery materials used in asphalt pavement as proposed in the above embodiment.

[0056] The computer device may be a terminal, and the computer device includes a processor, a memory, a communication interface, a display screen and an input device connected via a system bus. The processor of the computer device is used to provide computing and control capabilities. The memory of the computer device includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system and a computer program. The internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The communication interface of the computer device is used to communicate with an external terminal in a wired or wireless manner, and the wireless manner can be achieved through WIFI, an operator network, NFC (near field communication) or other technologies. The display screen of the computer device may be a liquid crystal display screen or an electronic ink display screen, and the input device of the computer device may be a touch layer covering the display screen, or a key, trackball or touchpad provided on the housing of the computer device, or an external keyboard, touchpad or mouse, etc.

[0057] This embodiment also provides a storage medium on which a computer program is stored. When the program is executed by a processor, the method for determining the dosage of solid waste powdery materials to be used in asphalt pavement as proposed in the above embodiment is implemented.

[0058] The storage medium proposed in this embodiment and the data storage method proposed in the above embodiment belong to the same inventive concept. The technical details not fully described in this embodiment can be found in the above embodiment, and this embodiment has the same beneficial effects as the above embodiment.

[0059] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for determining the dosage of solid waste powder materials used in asphalt pavement, characterized in that: The following steps are included: Prepare stone slabs of fixed size and treat the adhesive surface of the stone slabs; preparing adhesion performance test specimens; The adhesion performance test specimens were subjected to environmental coupling aging treatment; Conduct multi-point loading test on the adhesion performance test specimen and obtain test data; The optimal dosage of solid waste powdery materials as fillers in asphalt pavement materials is determined based on adhesion parameter indicators.

2. The method for determining the dosage of solid waste powdery materials in asphalt pavement according to claim 1, characterized in that: The steps for treating the adhesive surface of the stone slab include: The stone slab is cut using a laser cutting machine, and one side of the stone slab is used as the adhesive surface, and then it is polished using a CNC grinder. After polishing, the stone slab is placed in an ultrasonic cleaning machine and cleaned at 60°C for 20-30 minutes to remove powder and dust on the surface; Place the cleaned slab in a 100°C oven and dry for 1h-2h; Use a roughness meter to measure the roughness of the adhesion surface of the stone slab, and test the roughness of the center position of the adhesion surface and the midpoints of the four sides respectively. Take the average value of the test results as the roughness of the polished surface of the stone slab; When the roughness is less than 5μm, it meets the standard. When the roughness is not less than 5μm, the grinding is repeated until the roughness index meets the requirements. The prepared stone slabs are placed in an oven at 180°C-200°C for heating and standby use.

3. The method for determining the dosage of solid waste powdery materials in asphalt pavement according to claim 2, characterized in that: The steps of preparing the adhesion performance test specimen include: Preheat asphalt and solid waste powder materials to 135°C ± 1°C, weigh the solid waste powder according to the powder-to-binder mass ratio of 0.6, 0.8, 0.1, 1.2, and 1.4, add the weighed solid waste powder to the molten asphalt, and use a high-speed shearing instrument to shear the mixture at high speed to prepare solid waste powder-asphalt mortars with different powder-to-binder ratios; Take out the stone slab from the oven, place it in the 3D printer with the adhesive surface facing upward, pour the pre-prepared solid waste powder-asphalt slurry into the feed port of the 3D printer, and use the parallel printing mode to print an evenly distributed asphalt film with a thickness of 1-3mm on the adhesive surface of the stone slab. Then take out another stone slab from the oven, and attach it to the asphalt film with the adhesive surface facing downward to obtain the finished product; Place the finished product at the center of the rectangular tube, and place a steel plate on the finished product, and place a weight of 5-10kg at the center above the steel plate. Place the finished product, the rectangular tube, and the weight in a 60°C oven and let it stand for 1h-2h. When the steel plate and the rectangular tube are attached, the thickness of the asphalt film between the stone slabs no longer changes. At this time, take out the finished product and let it stand for 3-5h at room temperature. The thickness of the asphalt film was measured by a spiral micrometer, and the thickness of the asphalt film between the stone slabs was controlled at 1±0.05 mm. A hot scraper was used to scrape off the asphalt overflowing between the stone slabs to obtain the adhesion performance test specimen.

4. The method for determining the dosage of solid waste powdery materials in asphalt pavement according to claim 3, characterized in that: The steps of subjecting the adhesion performance test specimen to environmental coupling aging treatment include: Place the adhesion performance test specimen into the ultraviolet light accelerated weathering tester with the side facing the ultraviolet radiation light source; Manually adjust the placement of the adhesion performance test specimen every 82.5 hours, and change other sides to face the ultraviolet radiation light source, so that each side of the adhesion performance test specimen can be evenly exposed to ultraviolet aging; After aging, the adhesion performance test specimens were placed at room temperature for curing for 6-12 hours.

5. The method for determining the dosage of solid waste powdery materials in asphalt pavement according to claim 4, characterized in that: The steps to obtain test data include: The two tensile test molds 2 are bonded to the upper and lower surfaces of the adhesion performance test specimen using an epoxy resin adhesive; According to the requirements of different loading conditions, epoxy resin adhesive is evenly applied on the bottom and side surfaces of the loading point of the tensile test mold 1 to be bonded, and then bonded to the holes of the loading point on the upper end of the tensile test mold 2. After bonding, the tensile test mold 1 is fixed in a 20KN electro-hydraulic servo fatigue testing machine, and a cyclic dynamic load is applied to the morphological index specimen to simulate the repeated changes of the actual traffic load. Static loads are applied to the mechanical index specimen and the control specimen to test their bonding strength until the asphalt film between the adhesion performance test specimens is completely separated; The requirements for loading conditions include the first condition, the second condition, and the third condition.

6. The method for determining the dosage of solid waste powdery materials in asphalt pavement according to claim 5, characterized in that: The adhesion parameter index is the asphalt adhesion rate of the morphological index specimen under different loading conditions. , morphology index I1, mechanical index specimen failure work , mechanical index I2 and the failure work W of the control specimen 0i , aging resistance rate U i , aging index I3.

7. The method for determining the dosage of solid waste powdery materials in asphalt pavement according to claim 6, characterized in that: Methods for determining the optimal dosage of solid waste powder materials as fillers in asphalt pavement materials include: Draw radar charts of morphological index I1, mechanical index I2 and aging index I3; Calculate the area S of the radar chart and determine the optimal filler application amount of solid waste powdery materials by comparing the area sizes; Wherein, the asphalt adhesion rate The calculation formula is as follows: ; In the formula, is the asphalt adhesion rate, which represents the ratio of asphalt pixel area to total pixel area. The larger it is, the better the adhesion performance of the morphology index specimen; i is the number of different loading conditions; X1 and X2 are the pixel areas of asphalt on the upper and lower adhesion surfaces of the morphology index specimen; X is the sum of the pixel areas of the adhesion surface in the loading point images of the upper and lower adhesion surfaces of the morphology index specimen; The calculation formula of the morphology index I1 is as follows: ; In the formula, is the morphological index; is the average value of asphalt adhesion rate of the morphological index specimens under different loading conditions; is the average asphalt adhesion rate of the specimens with different solid waste powder content and morphological index The maximum value in ; is the average asphalt adhesion rate of the specimens with different solid waste powder content and morphological index The minimum value in ; The destructive work The calculation formula is as follows: ; In the formula, is the work of destruction, which represents the area under the load-displacement curve of the mechanical index specimen, and its unit is J. The larger the value, the better the adhesion performance of the mechanical index specimen; i is the number of different loading conditions; F(x) is the load as a function of displacement x in the load-displacement curve of the mechanical index specimen; L is the maximum destructive tensile force F in the load-displacement curve max The corresponding displacement in the load-displacement diagram; The mechanical index I2 is calculated as follows: ; In the formula, is the mechanical index; is the average value of the failure work of the mechanical index specimens under different loading conditions; is the average failure work of mechanical index specimens with different solid waste powder content The maximum value in ; is the average failure work of mechanical index specimens with different solid waste powder content The minimum value in ; The aging resistance rate U i The calculation formula is as follows: ; In the formula, is the aging resistance rate of the control specimen under different loading conditions; i is the number of different loading conditions; The failure work of the mechanical index specimen under different loading conditions; To compare the failure work of the specimen under different loading conditions; The calculation formula of the aging index I3 is as follows: ; in, is the aging index; is the average value of the aging resistance rate of the control specimens under different loading conditions; The average aging resistance rate of the control specimens with different solid waste powder dosages The maximum value in ; The average aging resistance rate of the control specimens with different solid waste powder dosages The minimum value in ; The calculation formula of the radar chart area S is: ; ; ; ; Among them, S is the total area of ​​the radar chart, with the center point of the radar chart as the origin O, the morphological index I1, mechanical index I2, and aging index I3 correspond to points A, B, and C on the radar chart, respectively. They are located on the ray starting from the origin, and the distances from the origin are a, b, and c, respectively; S OAB is the area of ​​the triangle formed by points O, A, and B in the radar chart; S OBC is the area of ​​the triangle formed by points O, B, and C in the radar chart; S OAC It is the area of ​​the triangle enclosed by points O, A, and C in the radar chart.

8. A system for determining the dosage of solid waste powdery materials used in asphalt pavement, based on the method for determining the dosage of solid waste powdery materials used in asphalt pavement according to any one of claims 1 to 7, characterized in that: It includes a slate preparation module, an adhesion performance test specimen preparation module, a multi-point loading test module, an environmental coupling aging treatment module, and an optimal dosage determination module; The slab preparation module is used to prepare slabs of fixed size and process the adhesion surface of the slabs; The adhesion performance test specimen preparation module prepares specimens for adhesion performance testing; The environmental coupling aging treatment module performs environmental coupling aging treatment on the adhesion performance test specimen; The multi-point loading test module performs a multi-point loading test on the adhesion effectiveness test specimen and obtains test data; The optimal dosage determination module determines the optimal dosage of solid waste powdery materials for use as fillers in asphalt pavement materials based on adhesion parameter indicators.

9. A computer device comprising a memory and a processor, wherein the memory stores a computer program, wherein: When the processor executes the computer program, the steps of the method for determining the dosage of solid waste powdery materials for asphalt pavement according to any one of claims 1 to 7 are implemented.

10. A computer-readable storage medium having a computer program stored thereon, characterized in that: When the computer program is executed by a processor, the steps of the method for determining the dosage of solid waste powdery materials used in asphalt pavement according to any one of claims 1 to 7 are implemented.

Citation Information

Patent Citations

  • Road maintenance gravel seal coat and production process thereof

    CN116623491A

  • Aggregate-asphalt adhesion evaluation method and system

    CN117741114A

  • Method and apparatus for separating bitumen from particulate substrates

    US20040129646A1